PEMBIAYAAN KREDIT PEMILIKAN RUMAH SYARIAH NON-BANK DI TAHFIDZ RESIDENCE - Dewi, Aulya Nur Rahmita; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2020)
The needs of human life are known to have three principles namely Sandang, Food, Board. The dense pace of growth causes the need for support, food, boards to increase, so there is a mortgage system that helps the population to get board needs. This research aims to find out the financing model used by Non Bank Sharia Home Owner Loans. Non-bank Sharia Home Owning Loans are essentially home loans for prospective home buyers who do not use banks in practice. The research method used is qualitatively descriptive. The results showed that the financing model of non-bank Sharia Home Owner Loans is not the same as Sharia Owner's Credit using banks. Murabahah and Mudharabah trading agreements used by non-bank Sharia Home Owner Loans are about the same as Sharia Home Owner Loans using banks.